The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1517/13543784.2012.685652
|View full text |Cite
|
Sign up to set email alerts
|

MF101: a multi-component botanical selective estrogen receptor beta modulator for the treatment of menopausal vasomotor symptoms

Abstract: Preclinical and clinical studies indicate that MF101, a selective estrogen receptor beta agonist, represents a new class of drugs that is safe and effective for treating HF and nighttime awakenings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…MF101 is an oral, botanically derived extract that selectively regulates ERβ, and is demonstrated by both preclinical and clinical data for its therapeutic promise for treating postmenopausal vasomotor symptoms without increasing cancer risks (Grady et al, 2009; Leitman and Christians, 2012). Our own research has provided further support for the therapeutic potential of an ERβ-based therapy for the improvement of both physical and neurological health during menopause (Zhao et al, 2009; Zhao et al, 2011a).…”
Section: Erβ-targeted Therapeutics For Ad and Beyondmentioning
confidence: 99%
“…MF101 is an oral, botanically derived extract that selectively regulates ERβ, and is demonstrated by both preclinical and clinical data for its therapeutic promise for treating postmenopausal vasomotor symptoms without increasing cancer risks (Grady et al, 2009; Leitman and Christians, 2012). Our own research has provided further support for the therapeutic potential of an ERβ-based therapy for the improvement of both physical and neurological health during menopause (Zhao et al, 2009; Zhao et al, 2011a).…”
Section: Erβ-targeted Therapeutics For Ad and Beyondmentioning
confidence: 99%
“…Our results showing that CC7 potentiates E2 transcriptional activation of ERβ might be a useful property to further prevent the proliferative effects of estrogens. We previously showed that the ERβ-selective plant extract 28 , MF101, reduced hot flashes in postmenopausal women, 29,30 suggesting another possible indication for CC7. Our findings suggest that an ERα coligand/estrogen combination could potentially provide superior safety to the estrogen only and estrogen/progestin regimens, and might make the current estrogens in MHT safe for long-term therapy to prevent chronic diseases associated with menopause.…”
Section: Discussionmentioning
confidence: 95%
“…To assess liquiritigenin content, a previously validated HPLC method was adapted for LC/MS use (15). The analytical column used was a Chiralpak ® AD-RH (150mm  4.6mm i.d., 5 To quantify pinostrobin, a second LC/MS method was developed from a previously validated HPLC method (17). Separation was achieved using a Chiralpak ® AD-RH (150mm  4.6mm i.d., 5-µm particle size, Chiral Technologies Inc. West Chester, PA, USA).…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Liquiritigenin (Figure 1) has recently been shown to be a highly selective estrogen receptor ß agonist (4). It is present in licorice species (Glycyrrhizae uralensis and Glycyrrhizae glabra) and has been identified as one of multiple active components in a proprietary botanical mixture called MF101 currently being tested in clinical trials for activity against menopausal vasomotor symptoms (5). Pinocembrin ( Figure 2) is present in the traditional medicinial plant Alpinia galangal and is notably recognized as the flavonoid of highest concentration in propolis, the resinous glue collected from plants by bees for use in hive building, and also a traditional medicine (6,7).…”
Section: Introductionmentioning
confidence: 99%